2019
DOI: 10.3892/ol.2019.10234
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication of ABC transporters and cancer stem cell markers in patients with stage III colon cancer receiving adjuvant FOLFOX‑4 chemotherapy

Abstract: Cancer stem cell (CSC) and ATP-binding cassette (ABC) transporters are associated with treatment resistance and outcomes of patients with cancer. The present study investigated the prognostic implications of pre-therapeutic expression of ABC transporters and CSC markers in patients with colon cancer (CC) who received adjuvant 5-fluorouracil, leucovorin and oxaliplatin combination therapy (FOLFOX-4). The immunohistochemical expression of 3 ABC transporters, including ABC subfamily C member 2 (ABCC2), ABCC3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…For example, in the future, the expression of SOX2 is defined as positive or negative, which should be recommended using a uniform standard. Fourth, only Han et al reported that SOX2 expression was correlated with DFS in 164 CRC cases (HR � 2.558, P � 0.020) [6]. Finally, sample sizes on the analyses between SOX2 expression and the clinicopathological features and the prognosis were relatively small in the meta-analysis, more studies with large study population are necessary to further determine whether SOX2 is correlated with clinical and prognostic value in CRC based on IHC methods.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…For example, in the future, the expression of SOX2 is defined as positive or negative, which should be recommended using a uniform standard. Fourth, only Han et al reported that SOX2 expression was correlated with DFS in 164 CRC cases (HR � 2.558, P � 0.020) [6]. Finally, sample sizes on the analyses between SOX2 expression and the clinicopathological features and the prognosis were relatively small in the meta-analysis, more studies with large study population are necessary to further determine whether SOX2 is correlated with clinical and prognostic value in CRC based on IHC methods.…”
Section: Discussionmentioning
confidence: 97%
“…SOX2 expression is correlated with the prognosis of some human cancers such as non-small cell lung cancer and cervical cancer with better prognosis [20,21] and breast cancer and gastric cancer with worse prognosis [18,19]. Studies have reported that SOX2 is frequently expression in CRC [6,34,35]. However, the function of SOX2 and its survival impact in patients with CRC are still largely uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations